Representasi Konflik Batin Tokoh Aurelie dalam Memoar Broken Strings: Teori Feminisme Psikoanalisis Keren Horney - Muhammad Rapi Tang; Nurul Azisyah Amini Amiruddin; Sri Yulianti; Nur Afnia; Nuriftitah Arsyad; Nurinayah Nurinayah (Universitas Nahdlatul Wathan Mataram, 2026)
The inner conflict experienced by women in manipulative relationships is often viewed as an individual problem, yet this experience is closely tied to the dynamics of power and social pressures that shape identity. The memoir, “Broken Strings: Pieces of Broken Youth,” depicts the psychological struggles of a woman who has endured emotional abuse and relational control. This study aims to analyze the representation of the protagonist’s inner conflict using Karen Horney’s feminist psychoanalytic theory, specifically the concepts of basic anxiety, neurotic needs, and the tension between the real self and the ideal self. This study employs a qualitative method with a descriptive-analytical approach. Data consisting of text excerpts from the memoir were analyzed through close reading, thematic categorization, and interpretation based on Horney’s theoretical framework. The results indicate that the character’s inner conflict stems from basic anxiety formed within an insecure relationship, subsequently developing through neurotic needs as defense strategies (approaching, rejecting, and withdrawing), and culminating in identity fragmentation manifested as self-rebellion, loss of self-autonomy, and feelings of worthlessness due to the gap between the authentic self and the ideal self created by patriarchal pressure. In the final phase, the character demonstrates a process of self-integration that marks a shift toward awareness and autonomy. This study affirms the relevance of Karen Horney’s theory in understanding women’s experiences in contemporary manipulative relationships and expands its application to autobiographical memoirs by illustrating the character’s psychological dynamics from identity fragmentation toward self-integration.